Drought-Tolerant Plant Growth-Promoting Rhizobacteria Associated with Foxtail Millet in a Semi-arid Agroecosystem and Their Potential in Alleviating Drought Stress - Niu, Xuguang; Song, Lichao; Xiao, Yinong; Ge, Weide (Frontiers in Microbiology, 2018)
The application of plant growth promoting rhizobacteria (PGPR) to agro-ecosystems is considered to have the potential for improving plant growth in extreme environments featured by water shortage. Herein, we isolated bacterial strains from foxtail millet (Setaria italica L.), a drought-tolerant crop cultivated in semiarid regions in the northeast of China. Four isolates were initially selected for their ability to produce ACC deaminase as well as drought tolerance. The isolates were identified as Pseudomonas fluorescens, Enterobacter hormaechei and Pseudomonas migulae on the basis of 16S rRNA sequence analysis. All of these drought-tolerant isolates were able to produce EPS (exopolysaccharide). Inoculation with these strains stimulated seed germination and seedling growth under drought stress. Pseudomonas fluorescens DR7 showed the highest level of ACC deaminase and EPS-producing activity. DR7 could efficiently colonize the root adhering soil, increased soil moisture, and enhance the root adhering soil/root tissue ratio. These results suggest drought tolerant PGPR from foxtail millet could enhance plant growth under drought stress conditions and serve as effective bioinoculants to sustain agricultural production in arid regions.